(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
It was in April 20, 2000, about 24 years ago, in Accra, Ghana, that the leaders of Six West African countries declared their intention to form a monetary union among the non-CFA franc countries of the region by January 2003, as a first step toward a wider monetary union that will include all the ECOWAS countries in 2004. The six (Nigeria, Ghana, Gambia, Guinea, Liberia and Sierra Leone) countries committed themselves to reducing central bank financing of budget deficits to 10 percent of the previous year's government revenue; reducing budget deficits to 4 percent of GDP by 2003; creating a Convergence Council to help coordinate macroeconomic policies; and setting up a common central bank. Their declaration states that, "Member States recognize the need for strong political commitment and undertake to pursue all such national policies as would facilitate the regional monetary integration process.This paper, using a historical approach, examined basic trends in reported data, tracing the performances of the nations for a period of 11 years (2012 to 2022) using the four primary convergence criteria according to the recommendations of ‘Optimum Currency Areas theory’ (Mundell, 1961), which was adopted by the promoters of the currency integration as the basis for the future prospects of the union. The performance data however, generally did not show evidence of a consistent trend towards the fulfillment of the adopted convergence criteria. The paper also noted the neglect of the private sector which can play major role in economic stability, through competition and recommended that economic managers of the region should convince their governments on the need to reduce public sector domination of the economy by channeling greater budgetary funds to the private sector, as is the tradition in advanced economies, for accelerated growth with stability.